Addition of Papain Enzyme to Pasta Feed with Different Doses and Times on the Growth and Survival of Jelawat Fish (Leptobarbus hoevenii) Larvae - Anjelina Sitorus; Nur Asiah; Benny Heltonika (Department of Aquaculture, 2026)
Jelawat fish (Leptobarbus hoevenii) is one of the indigenous fish species in Indonesia, with high economic value. The high selling price offers a potential for cultivation activities, as this fish has a large size and a delightful flesh taste that fulfills the community's taste preferences. This study aims to determine the effect of adding papain enzymes to pasta feed with different doses and times on the growth and survival of jelawat fish larvae. The method used in this study was a completely randomized design (CRD) factorial with 2 factors, namely: the first factor was the enzyme dose (0, 10 g, 20 g, 30 g), and the second factor was the time of administration (day 7 and day 10); each treatment was repeated 3 times. The parameters measured were absolute weight growth, absolute length growth, specific growth rate, survival, and water quality. The results showed that the enzyme dose, time of administration, and the interaction between dose and time had a significant effect (P<0.05) on the growth and survival of jelawat fish larvae. The best treatment was P4 (D10W10), resulting in absolute weight growth of 0.1229 g, absolute length of 1.50 cm, SGR of 7.83 %/day, and survival rate of 94.00%. Water quality parameters during the study were classified as optimal, specifically temperature 26.9 – 28.5 °C, pH 5.75 – 7.47, and DO 6.1 – 7.2 mg/L.